1998
DOI: 10.1046/j.1365-2923.1998.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism, the impostor phenomenon and psychological adjustment in medical, dental, nursing and pharmacy students

Abstract: Extensive attention has been paid over the past three decades to the stressors involved in training in the health professions. Although empirical studies have identified demographic subgroups of students most likely to become distressed during training, less research has been carried out to evaluate the impact of students' personality characteristics on their adjustment. Severe perfectionism is one such personality trait that has been shown to increase the risk for anxiety and depressive disorders in other pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
375
5
24

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 445 publications
(470 citation statements)
references
References 19 publications
30
375
5
24
Order By: Relevance
“…These high-standard environments include sports and exercise (Flett & Hewitt, 2005), education (Parker, 2002), professional achievement (Henning, Ey, & Shaw, 1998), and religion (Ashby & Huffman, 1999).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…These high-standard environments include sports and exercise (Flett & Hewitt, 2005), education (Parker, 2002), professional achievement (Henning, Ey, & Shaw, 1998), and religion (Ashby & Huffman, 1999).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Amidst these high standards, it is still possible to distinguish between maladaptive and adaptive forms of perfectionism, and maladaptive perfectionism has been linked to low self-esteem and interpersonal difficulties (Parker, 2002). A survey of medical, dental, pharmacy, and nursing students found greater levels of psychological distress were associated with perfectionism and the imposter phenomenon (Henning et al, 1998), and maladaptive perfectionism was found to predict symptoms of depression and hopelessness in another longitudinal study of medical students (Enns, Cox, Sareen, & Freeman, 2001). …”
Section: Perfectionism In Contextmentioning
confidence: 99%
“…Conversely, but equally destructive, is perfectionism, which derives from anxiety or self-esteem issues [8]. Perfectionism, and all its attendant negative effects on happiness, is a common consequence to deep feelings of inadequacy [5]. The same perfectionistic tendencies that drive a premedical student to ace all of his or her subjects, also puts them at risk for continual discontent and dissatisfaction.…”
Section: Listen To Your Bodymentioning
confidence: 99%
“…First, there is ample evidence that graduate medical education causes increases in psychological distress (including stress and anxiety) among medical students (Finkelstein, Brownstein, Scott, & Lan, 2007;Henning, Ey, & Shaw, 1998;Schmitter, Liedl, Beck, & Rammelsberg, 2008;Vitaliano, 1988;Vitaliano, Russo, Carr, & Heerwagen, 1984), yet there remains a limited amount of empirical evidence about the effects of this process on PA students (M. H. Brown, 2004;Childers et al, 2012;Glicken & Gray, 1993;Kuhn et al, 2005;O'Brien et al, 2012). Inquiry into whether similar outcomes exist among PA students would improve the understanding of educational practices among PA educators and provide a foundation on which to base informed curricular decisions.…”
Section: Significance Of This Projectmentioning
confidence: 99%
“…C. Clark & Zeldow, 1988;Dickstein, Stephenson, & Hinz, 1990;Helmers, Danoff, Steinert, Leyton, & Young, 1997;Roberts, 2010). It is well known that many students experience stress as part of a medical education process (Finkelstein et al, 2007;Henning et al, 1998;Schmitter et al, 2008), and stress has been recognized to have a negative effect on academic performance (Spiegel et al, 1986), health and psychological well-being (Helmers et al, 1997). High rates of stress, anxiety and depression have been reported in numerous articles on medical student mental health (D. C. Clark & Zeldow, 1988;Dahlin, Joneborg, & Runeson, 2005;Dyrbye, Thomas, Huntington et al, 2006;Schwenk, Davis, & Wimsatt, 2010;Vitaliano et al, 1984).…”
Section: Psychological Distress During the Process Of Medical Educationmentioning
confidence: 99%